Trace metals and oxidative status in soft tissues of caged mussels (Aulacomya atra) on the North Patagonian coastline - Ruiz, María Daniela (2018)
This study investigated metal accumulation and oxidative effects in mantle, gill and digestive gland of the ribbed mussel Aulacomya atra from the Argentinean North Patagonian coastline. Mussels were transplanted over an 18-month period from a site with low anthropogenic impact to a harbor site with higher seawater concentration of aluminum, chromium, copper, manganese, nickel and zinc. Total trace metal concentration in seawater did not change throughout the 18-month transplant in either site. A. atra bioaccumulated metals in digestive gland, gills and mantle at different levels. Digestive gland had the highest concentration of metals, especially towards the end of the transplant experiment in the harbor area. Mussels transplanted to the harbor site experienced an upregulation in their antioxidant system, which likely explains the lack of oxidative damage to lipids despite higher metal accumulation. These results demonstrate that A. atra selectively accumulates metals from the water column and their prooxidant effects depend on the tissue antioxidant defenses and the exposure time.